Epigallocatechin gallate and Lactobacillus plantarum culture supernatants exert bactericidal activity and reduce biofilm formation in Clostridium perfringens - Aguayo-Acosta, Alberto; Franco-Frías, Eduardo; Heredia, Norma; Merino-Mascorro, Jose A; Dávila-Aviña, Jorge E; Vidal, Jorge E; García, Santos (Folia microbiologica, 2021)
Clostridium perfringens forms biofilms and spores that are a source of food contamination. In this study, the antibacterial activities of Lactobacillus plantarum culture supernatants (LP-S), LP-S fractions, and the plant-derived compound epigallocatechin gallate (EG) were evaluated. Specifically, their effects on the viability and biofilm-forming ability of C. perfringens were assessed. Moreover, the expression of quorum sensing-regulated genes associated with the pathogenesis of this microorganism and that of genes involved in biofilm formation was also investigated. The results showed that both EG and the LP-S exerted bactericidal activity against all C. perfringens strains tested. The minimal bactericidal concentration (MBC) of EG was 75 µg/mL for all strains but ranged from 61 to 121 µg of total protein per mL for LP-S. EG exerted only minor effects on biofilm formation, whereas LP-S, particularly its 10 and 30 K fractions, significantly reduced the biofilm-forming ability of all the strains. The antibiofilm activity of LP-S was lost following preincubation with proteases, suggesting that it was mediated by a proteinaceous molecule. The treatment of C. perfringens with either EG or LP-S did not change the transcript levels of two CpAL (C. perfringens quorum-sensing Agr-like system)-related genes, agrB and agrD, which are known to be involved in the regulation of biofilms, suggesting that LP-S exerted its biofilm inhibitory activity downstream of CpAL signaling. In summary, we demonstrated the bactericidal activity of EG and LP-S against C. perfringens and antibiofilm activity of LP-S at a subinhibitory dose. Our results suggested that these compounds can be further explored for food safety applications to control agents such as C. perfringens.
Keywords: regulace genové exprese u bakterií; katechin; Lactobacillus plantarum; Catechin; Gene Expression Regulation, Bacterial; biofilmy; Biofilms; Culture Media, Conditioned; kultivační média speciální; Clostridium perfringens